Author Correction: Mechanochromism induced through the interplay between excimer reaction and excited state intramolecular proton transfer - Yu-Chen Wei (Nature Portfolio, 2019)
The original PDF and HTML versions of this Article contained errors in Eqs. (1) and (2). In both equations the approximately equal to symbol displayed incorrectly as ».  This has been corrected in both the PDF and HTML versions of the Article.